Systematic review and meta‐analysis of interventions targeting sleep and their impact on child body mass index, diet, and physical activity. Issue 5 (May 2016) - Yoong, Sze Lin; Chai, Li Kheng; Williams, Christopher M.; Wiggers, John; Finch, Meghan; Wolfenden, Luke
Abstract : Objective: This review aimed to examine the impact of interventions involving an explicit sleep component on child body mass index (BMI), diet, and physical activity. Methods: A systematic search was undertaken in six databases to identify randomized controlled trials examining the impact of interventions with a sleep component on child BMI, dietary intake, and/or physical activity. A random effects meta‐analysis was conducted assessing the impact of included interventions on child BMI. Results: Of the eight included trials, three enforced a sleep protocol and five targeted sleep as part of multicomponent behavioral interventions either exclusively or together with nutrition and physical activity. Meta‐analysis of three studies found that multicomponent behavioral interventions involving a sleep component were not significantly effective in changing child BMI ( n  = 360, −0.04 kg/m 2 [−0.18, 0.11], I 2  = 0%); however, only one study included in the meta‐analysis successfully changed sleep duration in children. There were some reported improvements to adolescent diet, and only one trial examined the impact on child physical activity, where a significant effect was observed. Conclusions: Findings from the included studies suggest that where improvements in child sleep duration were achieved, a positive impact on child BMI, nutrition, and physical activity was also observed.